Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Get immediate answers to your questions from a wide network of experienced professionals on our Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

Given f(x) = x^2 - 4x + 6 and g(x) = 2x^2 + 2x - 5, what is the equation for (f + g)(x)?


Sagot :

[tex]\\ \rm\Rrightarrow (f+g)(x)[/tex]

[tex]\\ \rm\Rrightarrow f(x)+g(x)[/tex]

[tex]\\ \rm\Rrightarrow x^2-4x+6+2x^2+2x-5[/tex]

[tex]\\ \rm\Rrightarrow 3x^2-2x+1[/tex]

Done!

Answer:

[tex](f+g)(x)=3x^2-2x+1[/tex]

Step-by-step explanation:

[tex]\begin{aligned}\textsf{Given functions}: \quad f(x) &=x^2-4x+6\\g(x) &=2x^2+2x-5\\\end{aligned}[/tex]

[tex]\begin{aligned}(f+g)(x) & =f(x)+g(x)\\& =(x^2-4x+6)+(2x^2+2x-5)\\& =x^2-4x+6+2x^2+2x-5\\& =x^2+2x^2-4x+2x+6-5\\& =3x^2-2x+1\end{aligned}[/tex]